Sex differences in cardiovascular, neuroendocrine and behavioral changes evoked by chronic stressors in rats - Vieira, Jonas O. [UNESP]; Duarte, Josiane O. [UNESP]; Costa-Ferreira, Willian [UNESP]; Morais-Silva, Gessynger [UNESP]; Marin, Marcelo T. [UNESP]; Crestani, Carlos C. [UNESP] (Elsevier, 2018)
This study investigated the physiological, somatic and behavioral changes evoked by daily exposure to the same type of stressor (homotypic) or different aversive stressor stimuli (heterotypic) in male and female rats. For this, adult Wistar rats were subjected to a 10 days regimen of repeated restraint stress (RRS, homotypic stressor) or chronic variable stress (CVS, heterotypic stressor). Effects evoked by CVS included: (i) adrenal hypertrophy and decreased body weight gain in male animals, (ii) a sympathetically-mediated increase in basal heart rate in males, and (iii) a rise in plasma corticosterone concentration and anxiogenic effects in female animals. The homotypic stressor RRS also induced an increase in plasma corticosterone and anxiogenic effects in females, decreased body weight gain in males and evoked a sympathetically-mediated increase in heart rate in both sexes. Changes in cardiovascular function and autonomic activity evoked by both stressors were followed by impairment of baroreflex activity in males, but not female animals. Both chronic stressors evoked changes in blood pressure responsiveness to vasoconstrictor and vasodilator agents in both sexes. Taken together, these results indicate that regardless of chronic stress regimen males are more vulnerable to somatic effects of chronic stressors, while females appear to be more susceptible to neuroendocrine and behavioral changes. Present findings also indicate that females are selectively vulnerable to cardiovascular and autonomic changes evoked by homotypic stressors. Nevertheless, homotypic and heterotypic stressors similarly affect cardiovascular function and autonomic activity in males.
Keywords: Autonomic activity; Baroreflex; HPA axis; Restraint stress; Unpredictable stress; Vascular